Keperluan memahami psikologi saudara muslim - Nur A‘thiroh Masyaa’il tan Binti Abdullah @ Tan Ai Pao Fariza Md, (Institut Islam Hadhari Universiti Kebangsaan Malaysia, 2009)
The principal approaches of Islamic civilization (Islam Hadhari) are giving upmost respect towards one individual. These include groups of Muslim converts called saudara Muslim. One who just converted to Islam will usually faces psychological challenges/ dilemma and needs the upmost understanding from the society surrounding them. The psychological aspect of Muslim converts is the most important aspect that needs to be address by the society. Muslim converts that have a peace of mind will eventually lead them to a good live. The unstable state of psychological will eventually make them live in stress and shaken their faith of converts. This article is to identify the phases of psychology faced by the Muslim converts, psychological challenges faced by them and the da’wah approaches that can help them in their lives as Muslim converts. This study is being conducted in fieldwork research and arm chair research. The results show that Muslim converts is experiencing five psychology phases: the phase of peace and calmness, conflict of faith phases, resistance in finding the right faith, phases of psychological pressure and back to peace and calmness phases. The psychological challenges being faced by Muslim converts includes understanding Islam as one religion, psychological pressure from the family, foster family and society and lastly psychological pressure in adapting into the new religions. The da’wah Islamiah approaches can help to overcome the psychological challenges being faced by the Muslim converts in order to achieve serenity in live which is called mutma’innah.